Factors and Determinants of Political Participation of Ethnic Groups - Fazulov, Azat (2022)
This paper discusses the problem of identifying factors and determinants of the political participation of ethnic groups in politics. Analysis of scientific literature allows us to identify several approaches to solving this problem. Some people view the political participation as an activity by which individuals try to influence the government through ethnic groups so that it takes the actions they want. This impact on the processes of political decision-making and the implementation of political programs related to them. Others believe that the driver of political activity is the need for internal improvement of an individual, when political participation contributes to their full functioning in the life of the state and gives them a sense of involvement in political processes. A comprehensive approach to determining the essence of the political participation of ethnic groups will be justified, according to which the institution of political participation is a multifaceted sociocultural phenomenon that affects many aspects of the socio-political dynamics of modern society. In accordance with this approach, political participation is equally manifested in both democratic and non-democratic political regimes; at the same time, the trigger of political mobilization can be not only the impact of political leaders, but also their own need for people to actively participate in political processes